Association between Mandibulofacial Asymmetry and Temporomandibular Disorder Using Diagnostic Criteria for Temporomandibular Disorder (DC/TMD) - Andriani, Agia T.; Purbiati, Maria; Krisnawati; Tanti, Ira (European Journal of Dentistry, 2025)
Mandibulofacial asymmetry can cause disharmony in facial appearance and smile and may also impair stomatognathic function and speech ability, negatively affecting psychological well-being and quality of life. This condition is also commonly associated with temporomandibular disorders (TMDs). This study aimed to analyze the relationship between mandibulofacial asymmetry and TMDs.This study conducted a cross-sectional study involving 42 patients (14 males and 28 females) aged 17 to 45 years. The diagnosis of TMDs was made using the Diagnostic Criteria for Temporomandibular Disorders, and facial asymmetry was assessed using frontal photography.The results showed that 76.2% of the patients with mandibulofacial asymmetry had a TMD. Statistical tests showed a relationship between mandibulofacial asymmetry and TMDs (p-value < 0.05).The TMD is closely related to mandibulofacial asymmetry. However, the relationship between mandibulofacial asymmetry and the specific categories of TMDs was not statistically significant, as determined by multinomial regression analysis.
Keywords: facial asymmetry; temporomandibular joint disorders; photography; diagnostic techniques and procedures; diagnosis